2014
DOI: 10.1016/j.diabres.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes on the natural history of tuberculosis

Abstract: Tuberculosis (TB) is the number one bacterial killer worldwide and the current increase in type 2 diabetes mellitus patients (DM), particularly in countries where TB is also endemic, has led to the re-emerging importance of DM2 as a risk factor for TB. There is an urgent need to implement strategies for TB prevention among the millions of DM patients exposed to Mycobacterium tuberculosis (Mtb) worldwide, but knowledge is limited on how and when DM2 alters the natural history of this infection. In this review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 68 publications
3
83
1
10
Order By: Relevance
“…The effect of pre-DM and DM on human immunity to M. tuberculosis during TB and LTBI Recent reviews have addressed the effect of DM on host response to M. tuberculosis 4,6,7 . Studies on human innate immune responses indicate that monocytes from poorlycontrolled DM patients (versus well-controlled or non-DM) have significantly lower binding M A N U S C R I P T…”
Section: Altered Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of pre-DM and DM on human immunity to M. tuberculosis during TB and LTBI Recent reviews have addressed the effect of DM on host response to M. tuberculosis 4,6,7 . Studies on human innate immune responses indicate that monocytes from poorlycontrolled DM patients (versus well-controlled or non-DM) have significantly lower binding M A N U S C R I P T…”
Section: Altered Immunitymentioning
confidence: 99%
“…It is increasingly clear that although TB and DM have different pathogenic mechanisms, they also share a number of similarities at the molecular level, including key pathways involved in chronic inflammation, metabolism and immunity. [3][4][5] It is critical to gain insight into the factors underlying the links between TB and DM at the molecular, cellular and systemic levels and to integrate data from clinical studies and animal models to better understand the fundamental causes and consequences of the comorbidity.…”
Section: Summary Boxmentioning
confidence: 99%
“…Diabetes is a barrier to tuberculosis elimination, particularly in Asian countries where the diabetes prevalence is rising [1][2][3]. Diabetes increases the risk for progression from latent Mycobacterium tuberculosis infection to active disease, and it increases tuberculosis severity.…”
mentioning
confidence: 99%
“…Its secretion was low in PTB when compared to HC in contrast to an Indonesian study where it was comparatively high [29]. A study by Jo et al [34] and Ludmila et al [5] reported that there was no statistical difference in the IL-6 production on stimulation with Ag85B and PPD in PTB patients and HCs and PTB HHC have not shown any variation from the HCs [35,36]. Our results were similar to a study where significantly higher levels were induced in PTB HHC when compared to PTB patients on proteomic analysis identification of immune-reactive T cell antigens [37].…”
Section: Discussionmentioning
confidence: 62%
“…Several co-morbidities, one of which is type 2 diabetes mellitus (DM) increased the risk of susceptibility to TB by threefold [2,3]. It is predicted that globally 15% of TB cases are projected to be attributable to DM thus becoming an increasingly important factor challenging TB control [4,5]. The immune response variation in DM patients against M.tb makes them more vulnerable to infection or progression towards active TB disease and thereby diminished treatment response [6,7].…”
Section: Introductionmentioning
confidence: 99%